Assessment of crenellation patterns of semen in Kal"an Fries bulls - MANDAL, AJOY; SHARMA, ARJAVA; RAMACHANDRAN, N (The Indian Journal of Animal Sciences, 2011)
Selnen sall1ples (303) from 20 Karan Fries bulls, between 4 to 6 years of age were evaluated to study the crenellation pattern of dried semen and its association with semen quality. Six grades (AI, A2, B1, B2, Cl and C2) of crenellation patterns were observed in all ej aculates. The seminal parameters varied significantly (P